Pengaruh Literasi Akuntansi dan Etika Individu terhadap Kecenderungan Kecurangan dengan Tekanan Finansial sebagai Pemoderasi - Yana Mustika; Senda Yunita Leatemia; Khalilul Rahman (AKUNTANSI 45, 2026)
This study is motivated by the increasing concern over fraud tendency in accounting-related contexts, particularly among individuals who possess accounting knowledge but may also face financial pressure. The study aims to examine the effect of accounting literacy and individual ethics on fraud tendency, with financial pressure as a moderating variable. This research employs a quantitative approach with an explanatory research design. The population consists of accounting students who have taken Financial Accounting and Auditing courses, while the sample comprises 100 respondents selected using accidental sampling. Data were collected through a Likert-scale questionnaire and analyzed using path analysis with SmartPLS. The findings indicate that accounting literacy and individual ethics have a negative and significant effect on fraud tendency, suggesting that higher accounting understanding and stronger ethical values reduce the likelihood of fraudulent behavior. Financial pressure has a positive and significant effect on fraud tendency. Furthermore, financial pressure significantly moderates the relationship between individual ethics and fraud tendency by weakening the preventive role of ethics, but it does not significantly moderate the relationship between accounting literacy and fraud tendency. These findings imply the importance of strengthening accounting literacy, ethical awareness, and financial pressure management as integrated fraud prevention strategies.